PL11.1 Global health legacies, sustainable development goals, and implications for sexual & reproductive health. (14th July 2019) - Peters, David
Abstract : In exploring the historical origins of global health – conceived as interventions in the health of other populations – this presentation identifies key themes that shape our thinking and action, including those related to sexual and reproductive health (SRH). The adoption of the 2030 Agenda for Sustainable Development and its Sustainable Development Goals (SDGs) offers a paradigm shift from the past. Using examples related to inequity, climate change, and migrant populations, the presentation examines the connections to and implications for SRH, identifying new opportunities and imperatives for action. Despite massive increases in the scale and complexity of global health efforts, the rationale and approaches for intervention have changed little, creating a legacy of: 1. Primacy of science. Advances in science in low resource settings have saved millions of lives around the world, yet has privileged biomedical and technological applications to addressing one health problem at a time, but with significant opportunity cost to building local capabilities and institutions 2. Short-termism. Interventions are designed in crisis or as simple 'quick wins', to the detriment of long-term, sustainable approaches that address coherent sets of issues facing populations or health systems 3. Neglect of underlying social, structural and commercial determinants of the health of populations The SDGs shift the focus towards tackling inter-dependent and often intractable problems that are both local and global, and demand a change in the approaches to global health and SRH interventions. Simply placing Universal Health Coverage as the center-piece of the SDGs is inadequate. Instead, emphasis is needed on greater participation by those most affected, and promoting coherence and integration beyond SRH programs or the health sector. Practical approaches would address linkages with economic opportunity, gender discrimination, education, water & sanitation, food security, environment and resource management, public safety, conflict management, disaster preparedness and other areas of development. Disclosure: No significant relationships.